Conceptualizing Contemporary Health Lifestyles. Moving Beyond Weber. - Rütten, Alfred; Cockerham, William C; Abel, Thomas (Sociological Quarterly, 1997)
The intent of this article is to move beyond the work of Weber and construct a concept of health lifestyles applicable to the current phase of modernity. Beginning with the early twentieth-century work of Simmel and Weber on lifestyles generally, we move to mid-century to examine Bourdieu's perspective and turn to Giddens for an analysis of late century conditions. We find that Weber's insight concerning the dialectical interplay of choice and chance remains the central feature of the lifestyle concept. We also suggest that in rapidly changing late or postmodern situations, lifestyles not only provide self-identity but also promote a sense of stability and belonging for an individual by providing an anchor in a particular social constellation of style and activity. Our discussion leads us to define health lifestyles as collective patterns of health-related behavior based on choices from options available to people according to their life chances. Consistent with Bourdieu's notion of habitus, we assign priority to chance (structure) over choic
UnivIS-Import:2015-03-05:Pub.1997.phil.dps.iss.lsw.concep